RESEARCH AND OPTIMIZATION OF FORMING PATH OF ELECTRON BEAM FUSE ADDITIVE MANUFACTURING——A CASE OF 304 STAINLESS STEEL - SUN BaoFu; XU BoHan; ZHANG LiPing; LI XiaoFeng; ZHANG JianFei; CHEN DongXue (Jixie qiangdu)
In this paper,using 304 stainless steel material 1 mm in diameter to fuse electron beam deposition rapid prototyping,by controlling the wire feed speed,electronic beam intensity and molding parameters such as the same,choose different forming path was 180 mm × 40 mm × 20 mm of print samples,after tensile test,Its microstructure and mechanical properties were observed and studied. By electron beam additive manufacturing,dense block material without macroscopic defects can be obtained. The average particle size of 304 stainless steel printed is no more than 10 μm,and contains fine uniform precipitation phase. Sample to print,staggered reciprocating print and improved staggered reciprocating print under the path of tensile strength of about 683 MPa,878 MPa,970 MPa,respectively the three print path molding samples can reach the hardness and tensile strength of 515 MPa or requirements,tensile fracture analysis,staggered print mode fracture to ductile fracture,staggered reciprocating type fracture to brittle fracture. The staggered reciprocating printing and the improved staggered reciprocating printing method have better density,better tensile strength and other mechanical properties.